REFRENSI SIBAWAIH DALAM KAJIAN ILMU NAHU - Bustamin Dihe (LP2M IAIN Sultan Amai Gorontalo, 2018)
When speaking of the source of the study of Sibawaih in the study of his nahu, we see the reference method of the grammatical method of the teachers of Si bawaih, namely the Qur'an and it's qira'a-t, Arabic poetry and language (Bedouin Arab). Sibawaih is also a central figure in the flow of blood and he follows many methods that his teacher uses, and has a very strong influence on his time. He is able to bring this grime flow to the peak of maturity and perfection. The main source which made Sibawaih as the basis of his methodology was that he followed the opinion of his teacher, as he had in his name with al-Kitab.